Desempenho no processamento de árvores e potencial energético de coproduto na colheita de eucalipto clonal - Gorte, Eloise Prates (2019)
The need for renewable energy production can directly influence the management of planted forests, through multi-products such as wood for industrial and energy purposes. In this context, the aim was to evaluate the tree processing operation and the energy potential of coproducts produced from different commercial height limit diameters in eucalyptus clonal stands. The research was carried out in a forestry company in the region of Campos Gerais, Paraná, Brazil, in clonal stands of Eucalyptus urophylla x Eucalyptus grandis and Eucalyptus saligna, both at 7 years-old under clearcutting. Four treatments defined by the commercial heights limits between pulp and coproducts were studied: T1-8 cm, T2-10 cm, T3-12 cm and T4-14 cm, as well as full trees for energy purposes (T5-FT). Initially, in Chapter I, the operational performance and quality assessment of the tree processing operation using the forest processor was performed, through a time-motion study. Then, in chapter II, the analysis of the energetic parameters of the coproducts generated from the processing of the trees, which were transformed into chips and taken to the laboratory for the determination of moisture, immediate chemistry and calorific power was carried out. The results showed that the operational performance of the forest processor was superior in the limit diameter of 10 cm, as well as presenting the best quality in the products produced. As for the energetic characteristics, it was found that E. saligna was the most susceptible clone to the treatments, due to the greater variations between the shares of the tree components (wood, bark, branches and leaves), being the best characteristics in the diameters above 10 cm. However, the hybrid E. urophylla x E. grandis presented constant energetic parameters in the different diameters, due to little variation between the participation of the tree components. Therefore, in general, the coproducts presented better quality parameters when they presented diameters equal or superior to 10 cm.